Debate. How should steps per day be reported--a proposal using data from Africa - Cook Ian (BMC, 2012)
Abstract Recent reviews published in the IJBNPA provide more definitive ranges of ambulatory activity usually found in four general age groups, and how step data relates to public health guidelines. Of note in these reviews was the lack of data from Developing Countries. Apart from the lack of published data, available data was not presented in a format conducive to inclusion in the reviews. Consequently, this paper presents available pedometry data from Africa, such that it is easily available for inclusion in future comparisons. Also addressed is the need to consider adjusting prevalence data according to standard population age structures.